Studies of the Sorption-Desorption of Pesticides from Cellulose-Based Derivative Nanocomposite Hydrogels - Tanaka, Fabrício C. [UNESP]; Yonezawa, Uilian G. [UNESP]; de Moura, Marcia R. [UNESP]; Aouada, Fauze A. [UNESP] (MDPI, 2024)
This study analyzed the effect of cellulose derivatives, namely methylcellulose (MC) and carboxymethylcellulose (CMC), on the stability of zeolite in a polymeric solution that would synthesize a three-dimensional network of poly(methacrylic acid)-co-polyacrylamide (PMAA-co-PAAm). Additionally, it investigated the effect of pH on the release of paraquat (PQ) and difenzoquat (DFZ) herbicides. Similar to previous studies with hydrogels containing CMC, the presence of bi and trivalent salts, such as Ca+2 and Al+3, also drastically reduced their swelling degree from 6.7 g/g in NaCl (0.15 mol·L−1) to 2.1 g/g in an AlCl3 solution (0.15 mol·L−1) for the MC nanocomposite. The viscosity results may suggest that the formation of a polysaccharide-zeolite complex contributed to the zeolite stabilization. As for the adsorption results, all samples adsorbed practically the entire concentration of both herbicides in an aqueous solution. Finally, it was also observed that the valence of the salts and molecular weight of the herbicide affect the release process, where DFZ was the herbicide with the highest concentration released. Both nanostructured hydrogels with CMC and MC exhibited lower release at pH = 7.0. These results demonstrated that a more in-depth evaluation of the phenomena involved in the application of these materials in controlled-release systems could help mitigate the impact caused by pesticides.
Keywords: agricultural area; cellulose derivatives; herbicides; hydrogel; zeolite